Correction: Optofluidic time-stretch imaging – an emerging tool for high-throughput imaging flow cytometry. Issue 11 (17th May 2017) - Lau, Andy K. S.; Shum, Ho Cheung; Wong, Kenneth K. Y.; Tsia, Kevin K.
Abstract : Correction for 'Optofluidic time-stretch imaging – an emerging tool for high-throughput imaging flow cytometry' by Andy K. S. Lau et al., Lab Chip, 2016, 16, 1743–1756.